Dual attribution and shared responsibility of an international organization and a state - Novashok, D. O. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article examines the issue of dual attribution of an internationally wrongful act simultaneously to both a state and an international organization. It is established that when one and the same internationally wrongful act is attributed to both subjects, shared international legal responsibility arises. Shared responsibility has important implications for the content of such responsibility, as the obligations to cease the wrongful act and to make reparation may be shared among multiple responsible actors, and the injured party may seek cessation or reparation from each of them. It is found that the norms of international law, particularly the 2011 Draft Articles on the Responsibility of International Organizations, allow for the possibility of dual attribution, but do not in any way regulate the specific features of the distribution of responsibility arising from it. The analysis shows that, in the context of dual attribution of conduct, two rules of attribution are particularly important. One is attribution based on the existence of an organic de jure link between the organ or agent that committed the internationally wrongful act and the subject – be it a state or an international organization. The other rule of attribution that plays an important role in the context of dual attribution is attribution based on the exercise of effective control by the subject over the organ or agent. The article outlines the situations in which dual attribution may occur and, accordingly, shared responsibility of the state and the international organization may arise. First, dual attribution may occur when the organ or agent that committed the internationally wrongful act has a de jure connection with both the state and the international organization. Second, shared responsibility may arise in situations where the organ or agent has an organic de jure link with the international organization but is under the effective control of the state at the time the internationally wrongful act is committed. At the same time, it is determined that shared responsibility arises not only from dual attribution of conduct but also in cases of derivative responsibility, particularly in situations involving aid or assistance, direction and control, coercion, as well as circumvention of obligations.